Comparison of Dapaglifozin and Liraglutide in Patients with Poorly Controlled Type 2 Diabetes Mellitus: a 24-week, Open, Double-centered, Head to Head Trial - Jiang, Jianjia; Lin, Lu; Chen, Pin (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Objective: To evaluate the efficacy and treatment satisfaction of dapagliflozin and liraglutide in T2DM patients with glucose poorly controlled after triple therapy. Methods: In addition to the original therapeutic regimen, dapagliflozin (n=83) and liraglutide (n=89) once a day were added, respectively. Height, body weight, waist circumference, and blood pressure were recorded. FBG, 2hPBG, HbA1c, fasting C-peptide, HOMA-IR, blood lipid, eGFR, BUA and DTSQ were detected before the treatment and after 24 weeks of treatment. Results: At the end of 24 weeks of treatment, a follow-up visit was completed for 79 patients in the dapagliflozin group and 77 patients in the liraglutide group. The body weight of the patients in the dapagliflozin group and the liraglutide group decreased significantly (P<0.05). The HbA1c level in the dapagliflozin group decreased from 8.96 ± 1.23% to 7.03 ±0.74% (P< 0.01), more than that in the liraglutide group, namely, from 8.99 ± 1.34% to 7.24 ±0.77% (P< 0.01). After 12 weeks of treatment, eGFR in the dapagliflozin group first decreased and then increased after 12 weeks of treatment. The percentages of patients achieving combined endpoints in the two groups were of no statistical significance (P=0.204). And there were mild adverse events in both groups. Conclusion: The add-on treatment of dapagliflozin and liraglutide had promising clinical outcomes in patients with T2DM and poorly controlled glucose after triple therapy, which include the improvement in blood glucose, insulin resistance, SBP, and renal function. However, the overall treatment satisfaction was higher in the dapagliflozin group.
Keywords: Liraglutide